2010
DOI: 10.1002/adsc.200900789
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Three‐Step Synthesis of Naphtho[2,3‐a]carbazole‐ 5,13‐diones using a Tandem Radical Alkylation–Cyclization– Aromatization Reaction Sequence

Abstract: A three-step, one-pot tandem reaction including radical nucleophilic alkylation/cyclization/ aromatization was developed using 0.3 equivalents of silver(I) acetate (AgOAc) as the catalyst and 2 equivalents of ammonium persulfate [(NH 4 ) 2 S 2 O 8 ] as the oxidant. This strategy is highly efficient for the assembly of pentacyclic complex carbazoles from aryl-fused bromobenzoquinones and indol-3-ylpropanoic acid acids in 52-72% overall yields (three steps). This new approach provides a significant improvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
(28 reference statements)
1
12
1
Order By: Relevance
“…Reaction optimisation, through systematic variation of numerous reaction parameters using the unsubstituted 3-phenylpropionic acid 12, in a Design of Experiments (DoE) approach (further information provided in the S1 File), led to improved yields of around 40%, including a 42% yield of alkylation product 11. Throughout these studies, although formation of a small quantity (< 10%) of doubly-alkylated product was observed, none of the alternative mono-alkylated product (alkylated adjacent to the methoxide group) was seen, which was consistent with previous reports, and likely a directing effect due to the bromide substituent [66,68].…”
Section: Chemical Synthesis Of Ti Analogues and Isomerssupporting
confidence: 91%
“…Reaction optimisation, through systematic variation of numerous reaction parameters using the unsubstituted 3-phenylpropionic acid 12, in a Design of Experiments (DoE) approach (further information provided in the S1 File), led to improved yields of around 40%, including a 42% yield of alkylation product 11. Throughout these studies, although formation of a small quantity (< 10%) of doubly-alkylated product was observed, none of the alternative mono-alkylated product (alkylated adjacent to the methoxide group) was seen, which was consistent with previous reports, and likely a directing effect due to the bromide substituent [66,68].…”
Section: Chemical Synthesis Of Ti Analogues and Isomerssupporting
confidence: 91%
“…34 These carbazoles are formed via a radical/radical/radical/oxidation/anionic/oxidation domino process. This transformation begins by oxidation of Ag(I) to Ag(II), which then oxidizes 90 to a carboxy radical ( 93 ).…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…[11] A one-pot synthesis of carbazolonaphthoquinones was realized in a three-step tandem radical alkylation/cyclization/aromatization reaction sequence. [12] Very recently, highly efficient one-pot syntheses of carbazoles and dihydrobenzo [a]carbazoles were reported that involve Pd-mediated domino reactions. [13,14] The synthesis of annulated heterocycles 2 (Scheme 1) by domino reaction of benzylic bromo compounds 1 containing a malonylidene unit with arenes and heteroarenes in the presence of a Lewis acid has been reported by our laboratory.…”
Section: Introductionmentioning
confidence: 99%